American Society of Adlerian Psychology records - American Society of Adlerian Psychology
Correspondence, minute books, membership lists, organizational material, and other records relating to the history and incorporation of the society.
Society founded in 1951 to foster and promote the research, knowledge, training, and application of Adlerian psychology based on the work and teachings of Alfred Adler. Renamed the North American Society of Adlerian Psychology in 1977.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adler, Alfred, -- 1870-1937.; Adlerian psychology; Psychology -- United States